PAKANI: Sustainable of Blue Economy melalui Islamic Digital Platform dalam Upaya Memberdayakan Petani Ikan di Jawa Timur - Dwi Seftiana Ananda Sarno, Fajar (Reinforce: Journal of Sharia Management, 2024)
This study examines digital innovation through the PAKANI platform as a solution to support the implementation of a sustainable blue economy concept and empower fish farmers in East Java. PAKANI is designed as a technology-based application that provides comprehensive access to sharia financing, affordable and quality fish feed distribution, and broader marketing access for small-scale fish farmers. Challenges faced by fish farmers in East Java include limited resource access, high production costs, and inefficient distribution. This study employs a qualitative approach with descriptive analysis based on literature from journals, books, scientific reports, and articles to analyze East Java’s geographical potential for inland aquaculture in underutilized lands. The findings show that PAKANI can act as a catalyst in enhancing productivity and sustainability in small-scale aquaculture, particularly through integrating digital technology and sharia-compliant financing that is accessible for fish farmers. The blue economy concept applied in this platform leverages technology to reduce resource waste and support sustainable aquaculture practices aligned with circular economy principles. These findings are expected to make a significant contribution to the academic literature on digitalization in the aquaculture sector and the inclusive development of sharia-based economies, particularly in Indonesia. This platform is anticipated to improve fish farmers’ welfare and increase the fisheries sector’s contribution to sustainable economic growth in Indonesia.